Bacillus subtilis e Trichoderma harzianum na qualidade e na ocorrência de antracnose em frutos de banana - Viencz, Thayna (2019)
The objective of the research was to evaluate the efficiency of Trichoderma harzianum and Bacillus subtilis in the post-harvest control of anthracnose, in the antioxidative system and in the post-harvest quality of 'Nanicão' banana fruits. In vitro and in vivo tests were performed. The fruits destined to the in vivo tests were harvested on 7/13/2018 in an orchard located in the municipality of Novo Itacolomi-PR, and underwent air conditioning. In all experiments a completely randomized design was used. The in vitro evaluations consisted of the pairing of C. musae with T. harzianum and B. subtilis, and in the spore germination test, both performed in duplicate. Treatments were as follows: control, Trichoderma harzianum, Bacillus subtilis and thiabendazole. The effect of treatments on C. musae was evaluated by daily measurement of mycelial growth. The effect of treatments on spore germination of C. musae was evaluated by counting in each well on the Elisa test plate. To verify the effects of treatments on anthracnose control, the incidence (AUPCI) and severity (AUPCS) were evaluated daily. Treatments were as follows: control without inoculation, control with inoculation, Trichoderma harzianum, Bacillus subtilis, Trichoderma harzianum + Bacillus subtilis and thiabendazole. In order to evaluate the effects of the treatments on the post-harvest quality of fruits, mass loss, staining, pulp firmness, soluble solids, titratable acidity, pH and the ratio (SS/TA) were evaluated. The effects of the treatments in the antioxidative system were also evaluated by the peroxidase enzyme activity, in addition to the lipid peroxidation. Based on the results, the application of T. harzianum in 'Nanicão' banana fruits was efficient in controlling the severity of rot caused by Colletotrichum musae, although the biological agent B. subtilis was not efficient in this process. In the antioxidative system no significant effects were observed for both biological agents. In the postharvest quality, the treatments with biocontrol agents did not show satisfactory effect on the fruits.